if m=tan theta+ain't theta and n=tan theta-sin theta then m square-n square
Answers
Answered by
18
==================================
⭐⭐⭐⭐⭐ ANSWER ⭐⭐⭐⭐⭐
==================================
Given, m = tan theta + sin theta
n = tan theta - sin theta
Now here, I am holding "THETAS" as "x".
So, mn = (tan x + sin x) (tan x - sin x)
=> mn = tan²x - sin²x
=> mn = (sin²x/cos²x) - sin²x
=> mn = sin²x (1/cos²x - 1)
=> mn = sin²x (1-cos²x/cos²x)
=> mn = sin²x (sin²x/cos²x)
=> mn = sin²x tan²x
=> mn = (sin x tan x)²
=> √mn = sin x tan x
Therefore, m²-n²
= (tan x + sin x)² - (tan x - sin x)²
= tan²x + 2 sin x tan x + sin² x - tan²x + 2 tan x sin x - sin² x
= 2 sin x tan x + 2 sin x tan x
= 4 sin x tan x
= 4 √mn [REQUIRED ANSWER]
THUS, THE QUESTION GETS SOLVED (^_^)
==================================
⭐⭐⭐ ALWAYS BE BRAINLY ⭐⭐⭐
==================================
⭐⭐⭐⭐⭐ ANSWER ⭐⭐⭐⭐⭐
==================================
Given, m = tan theta + sin theta
n = tan theta - sin theta
Now here, I am holding "THETAS" as "x".
So, mn = (tan x + sin x) (tan x - sin x)
=> mn = tan²x - sin²x
=> mn = (sin²x/cos²x) - sin²x
=> mn = sin²x (1/cos²x - 1)
=> mn = sin²x (1-cos²x/cos²x)
=> mn = sin²x (sin²x/cos²x)
=> mn = sin²x tan²x
=> mn = (sin x tan x)²
=> √mn = sin x tan x
Therefore, m²-n²
= (tan x + sin x)² - (tan x - sin x)²
= tan²x + 2 sin x tan x + sin² x - tan²x + 2 tan x sin x - sin² x
= 2 sin x tan x + 2 sin x tan x
= 4 sin x tan x
= 4 √mn [REQUIRED ANSWER]
THUS, THE QUESTION GETS SOLVED (^_^)
==================================
⭐⭐⭐ ALWAYS BE BRAINLY ⭐⭐⭐
==================================
Similar questions